STUDY ON THE INFLUENCE OF DIFFERENT LUBRICATION STATES ON BENDING FATIGUE CHARACTERISTICS OF WIRE ROPE (MT) - WANG ShaoLei; WANG ZhanYing; LI Xin; LIANG JianMing; ZHU ChunHua (Jixie qiangdu)
The lubrication state of wire rope has an important influence on the working characteristics and fatigue life of wire rope. 6X19 steel wire rope is taken as the research object, and three kinds of steel wire rope without grease lubrication, partially lubrication and fully lubrication are selected. The bending fatigue tests are carried out on the bending fatigue test machine under different tension states, and the fatigue damage states of each specimen in different stages are statistically analyzed and microscopic studied. Under good lubrication condition, between wire rope and pulley rope groove of the oil film to improve the contact state, reduce the friction coefficient between steel wire rope, steel wire surface is not easy to wear and tear scratches, delay the formation and extension of cracks and improve the steel wire rope section stress distribution and reduce the stress concentration phenomenon, make more effective load effect on the number of steel wire. The steel wire in the rope is fully drawn, and the proportion of necked broken wire in the total broken wire is higher than that of the wire rope with poor lubrication condition. For the wire rope with poor lubrication condition, the proportion of flush fracture is high, and the steel wire in the rope is not fully drawn, resulting in wire breakage due to local damage. Under the same lubrication condition, the increase of tension force destroys the lubricating oil film between the wire rope and pulley groove on the one hand, on the other hand, under the action of compressive stress, the lubricating oil in the rope core is not easy to infiltrate into the side of the wire rope and pulley groove, which deteriorates the lubrication state.